PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Zuraida, Zuraida (Jurnal Pendidikan Guru, 2018)
Problem in this research was students achievement as still low. In this application of cooperative learning model Think Pair Share students were more motivated to learn in a group while learning about a concept or topic, in a happiness atmosphere, in addition to the training accuration too, precision and accuracy as well as speed. This research is classroom action research (CAR) with research subjects the Student at class V SD Negeri 20 Pekanbaru 2015/2016. The purpose of this research is to improve students achievement at mathematics the students class V SD Negeri 20 Pekanbaru with the cooperative learning model Think Pair Share implementation. The data in this research is the quantitative data obtained from the data on the activities of teacher and students through observation and data test students knowledge and understanding through daily test. Results of this research showed that the average percentage of all teacher in the first cycle was 72,3% (Category: Good), the second cycle was 83,4% (Category:Very Good) and the third cycle is 93,1% (Category: Very Good). While the percentage of students learning activity in the first cycle was 72,3% (Category: Good), the second cycle was 81,9% (Category: Very Good) and the third cycle to 90,3% (Category: Very Good). Average students learning outcomes in basic score is 55,83 increased to 68,63 in the first cycle, increasing again to 83,3 in the second cycle and increased to 86,6 in the third cycle. While the classical completeness in the second cycle and the third cycle is reached. This means that the cooperative learning model Think Pair Share (TPS) implementation can increase students achievement at Mathematics in class V SD Negeri 35 Pekanbaru.